Types of Plurality and Their Representation in Kabardian-Circassian Language - B. Ch. Bizhoev; M. R. Khezheva (Научный диалог)
This study investigates the methods and means of representing the semantics of plurality in the Kabardian-Circassian language. Affixal, lexical, and phraseological resources for expressing specific, indefinite, approximate, total, collective, and representative plurality within the Adyghe linguistic consciousness have been identified, systematized, and characterized. It is noted that among all the mentioned types of plurality, the semantics of representative plurality is the most extensively studied in the Kabardian-Circassian language. The research demonstrates that quantifiers with universal semantics in Kabardian-Circassian can express both discrete and non-discrete pluralities. The scientific novelty of this research lies in the fact that it is the first attempt in Adyghe linguistics to systematically categorize various ways of representing the semantics of plurality across all levels of the linguistic system. It has been established that the representation of imprecise pluralities exhibits considerable diversity. For instance, it is shown that in fixed expressions and the phraseological layer of the language, numeratives lose their specific quantitative meaning and serve as representatives of indefinite plurality. The investigation of phraseological units reveals that in the Adyghe worldview, the semantics of plurality is often realized through the functional involvement of entomosemisms. The findings can be applied to the study of issues related to linguistic expression of quantity semantics.